Tn5 mutagenesis of Anabaena sp. strain PCC 7120: isolation of a new mutant unable to grow without combined nitrogen. - Borthakur, D (1989)
Methylation by Ava methylases in Escherichia coli increases the efficiency to transfer of Tn5 in pBR322bla:: Tn5 from E. coli to Anabaena sp. strain PCC 7120 by conjugation. Following conjugation, Tn5 but not pBR322 sequences were found at many different positions in the Anabaena chromosome. This procedure was used to mutagenize, tag, and clone a previously unrecognized gene required for nitrogen fixation in this Anabaena sp.